An Asp376Glu substitution in ALS gene and enhanced metabolism confers high tribenuron-methyl resistance in Sinapis alba - Palma-Bautista, Candelario; Vázquez-García, José G.; Osuna, Maria D.; Garcia-Garcia, Blanca; Torra, Joel; Portugal, Joao; De Prado, Rafael (Frontiers in Plant Science, 2022)
Acetolactate synthase (ALS) inhibiting herbicides (group 2) have been widely applied for the last 20 years to control Sinapis alba in cereal crops from southern Spain. In 2008, a tribenuron-methyl (TM) resistant (R) S. alba resistant (R) population was first reported in a cereal field in Malaga (southern Spain). In 2018, three suspected R S. alba populations (R1, R2 and R3) to TM were collected from three different fieldsa cereal field in Granada (southern Spain, 100 km away from Malaga). The present work aims to confirm the putative resistance of these populations to TM and explore their resistance mechanisms. Dose–response assays showed that the R1, R2 and R3 populations ranging between 57.4, 44.4 and 57.1 times more resistance to TM than the susceptible population (S). A mutation in the ALS gene (Asp376Glu) was detected in the Rs S. alba populations. 14C-metabolism studies show that metabolites and TM were changing significantly faster in the R than in the S plants. Alternative chemical control trials showed that 2,4-D and MCPA (auxin mimics), glyphosate (enolpyruvyl shikimate phosphate synthase,EPSPS, inhibitor-group 9), metribuzin (PSII inhibitors/Serine 264 Binders, -group 5PS II inhibitor) and mesotrione (hydroxyphenyl pyruvate dioxygenase, HPPD, inhibitor-group 27) presented a high control of the four populations of S. alba tested, both S as and R. Based on these results, it is the first case described where the Asp376Glu mutation and P450-mediated metabolism participates in resistance to TM in S. alba. Comparing these results with those found in the S. alba population in Malaga in 2008, where the resistance was TSR type (Pro197Ser), we can suggest that despite the geographical proximity (over 100 km), the resistance in these cases was due to different evolutionary events.